2012
DOI: 10.1186/1546-0096-10-6
|View full text |Cite
|
Sign up to set email alerts
|

MR enterography to evaluate sub-clinical intestinal inflammation in children with spondyloarthritis

Abstract: BackgroundMagnetic resonance enterography (MRE) is an established tool to evaluate for changes associated with inflammatory bowel disease (IBD), but has not been studied in sub-clinical IBD. We sought to evaluate the use of MRE in children with spondyloarthritis (SpA), who are at risk of having sub-clinical gut inflammation.MethodsChildren with juvenile idiopathic arthritis (JIA) with evidence of intestinal inflammation as evidence by an abnormal fecal calprotectin assay were offered MRE of their intestines. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 22 publications
(20 reference statements)
0
11
0
Order By: Relevance
“…Interestingly, elevated levels of fecal calprotectin, a marker of intestinal inflammation, were seen in a small series of ERA patients compared to healthy, other JIA, and other connective tissue disease controls 37 . In a follow-up study, MR enterography performed on 5 patients with JIA and elevated fecal calprotectin, including 4 with jSpA, showed evidence of intestinal inflammation 38 .…”
Section: Clinical Featuresmentioning
confidence: 96%
“…Interestingly, elevated levels of fecal calprotectin, a marker of intestinal inflammation, were seen in a small series of ERA patients compared to healthy, other JIA, and other connective tissue disease controls 37 . In a follow-up study, MR enterography performed on 5 patients with JIA and elevated fecal calprotectin, including 4 with jSpA, showed evidence of intestinal inflammation 38 .…”
Section: Clinical Featuresmentioning
confidence: 96%
“…Specifically, Picco et al (2000) used the urinary lactulose/mannitol test to demonstrate altered intestinal permeability in children with JIA (28); they found it was higher in children with juvenile spondyloarthritis (SpA) compared to those with other forms of JIA, who themselves had higher levels than healthy control subjects. Several additional studies have identified evidence of sub-clinical intestinal inflammation in children with spondyloarthritis using colonoscopy (29), fecal calprotectin (30), or MRI (31); all of these studies suggest children with at least the SpA variant of JIA may have qualitatively similar, while quantitatively less, intestinal abnormalities as patients with inflammatory bowel disease (IBD). Conversely, it is well-established that up to one quarter of patients with IBD has arthritis, typically SpA (32).…”
Section: Alterations In the Microbiome In Pediatric Rheumatic Diseasesmentioning
confidence: 99%
“…Elevated fecal calprotectin, a marker of gut inflammation, has been found in patients with ERA as compared to other JIA subtypes, healthy, or other connective tissue diseases in childhood, and such patients have been demonstrated to have a MRI evidence of gut inflammation [24].…”
Section: Extra-articular Featuresmentioning
confidence: 99%